2020
DOI: 10.1093/femsyr/foaa022
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Pca1 in ROS-mediated apoptotic cell death induced by alpha-thujone in the fission yeast (Schizosaccharomyces pombe)

Abstract: Alpha-thujone, widely used in beverages (1–5 mg/kg), is known to have cytotoxic effects, but the mode of action and the role of potential apoptotic proteins in yeast cell death should be unraveled. In this study, we used Schizosaccharomyces pombe, which is a promising unicellular model organism in mechanistic toxicology and cell biology, to investigate the involvement of pro-apoptotic factors in alpha-thujone-induced cell death. We showed alpha-thujone-induced ROS accumulation-dependent cytotoxicity and apopto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 56 publications
0
8
2
Order By: Relevance
“…Still, although yca1 Δ cells are more resistant to acetic acid than the wild-type strain in terms of cell survival, multiple studies showed no significant difference in apoptotic markers such as chromatin condensation ( Guaragnella et al, 2006 ), DNA fragmentation ( Guaragnella et al, 2010a ; Longo et al, 2015 ) or mitochondrial fragmentation ( Longo et al, 2015 ), though Yca1p was required for cytochrome c to be released from mitochondrial reservoirs ( Guaragnella et al, 2010a ). In S. pombe , acetic acid treatment increased mRNA levels of pombe caspase-1 ( PCA1) and acridine orange/ethidium bromide (AO/EtBr) staining, but authors showed only increased growth of pca1 Δ cells on plates containing acetic acid, not protection from cell death ( Agus et al, 2020 ). Of note, as discussed above, the caspase-like activity observed in acetic acid-treated cells ( Pereira et al, 2007 ; Aerts et al, 2009 ; Guaragnella et al, 2010a , b , 2011 ; Lastauskienë et al, 2014 ; Saraiva et al, 2006 ) may be a consequence and not a direct mediator of the cell death process.…”
Section: Genetic Modulation Of Acetic Acid-induced Regulated Cell Deathmentioning
confidence: 99%
“…Still, although yca1 Δ cells are more resistant to acetic acid than the wild-type strain in terms of cell survival, multiple studies showed no significant difference in apoptotic markers such as chromatin condensation ( Guaragnella et al, 2006 ), DNA fragmentation ( Guaragnella et al, 2010a ; Longo et al, 2015 ) or mitochondrial fragmentation ( Longo et al, 2015 ), though Yca1p was required for cytochrome c to be released from mitochondrial reservoirs ( Guaragnella et al, 2010a ). In S. pombe , acetic acid treatment increased mRNA levels of pombe caspase-1 ( PCA1) and acridine orange/ethidium bromide (AO/EtBr) staining, but authors showed only increased growth of pca1 Δ cells on plates containing acetic acid, not protection from cell death ( Agus et al, 2020 ). Of note, as discussed above, the caspase-like activity observed in acetic acid-treated cells ( Pereira et al, 2007 ; Aerts et al, 2009 ; Guaragnella et al, 2010a , b , 2011 ; Lastauskienë et al, 2014 ; Saraiva et al, 2006 ) may be a consequence and not a direct mediator of the cell death process.…”
Section: Genetic Modulation Of Acetic Acid-induced Regulated Cell Deathmentioning
confidence: 99%
“…In addition, β-pinene and 1,8-cineole (present in significant amounts in both sage and bay laurel essential oils) were positively correlated with the inhibition of S. parasitica zoospore germination, explaining the similar EC 50 values of these two essential oils for S. parasitica zoospore germination (EC 50 0.012 and 0.013 µL/mL, respectively). Some of these compounds were previously reported to exhibit good anti-oomycete [ 44 , 55 ] and antifungal [ 56 , 57 , 58 , 59 ] activity. For example, camphor (up to 38.06 µg/mL) progressively slowed down the mycelial growth of S. parasitica and S. delica , while thujone and β-pinene (500 and 1000 µg/mL, respectively) inhibited the mycelial growth of S. parasitica [ 44 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, camphor (up to 38.06 µg/mL) progressively slowed down the mycelial growth of S. parasitica and S. delica , while thujone and β-pinene (500 and 1000 µg/mL, respectively) inhibited the mycelial growth of S. parasitica [ 44 , 55 ]. Moreover, α-thujone and camphor have potent antifungal activity against Fusarium graminearum , F. culmorum , and Schizosaccharomyces pombe , which is mainly explained by the induction of oxidative stress and subsequent apoptotic cell death, but also by a decrease in genomic stability and epigenetic changes [ 56 , 57 , 58 , 59 ]. Thus, the high camphor content in sage essential oil probably contributed significantly to the observed inhibitory effects.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, dga1 plh1 double mutant, which is defective in lipid metabolic pathway, promotes apoptosis in stationaryphase [29,30]. Also, some compounds such as terpinolene [27] and alpha-thujone [21] induce apoptosis in this organism.…”
Section: Introductionmentioning
confidence: 99%
“…Fission yeast Schizosaccharomyces pombe is a powerful model organism to study apoptosis [21][22][23][24] and autophagy [25,26]. Apoptosis is detectable in fission yeast by observing dead cells and nuclear fragmentation [24,27,28] that could be induced by different conditions.…”
Section: Introductionmentioning
confidence: 99%